Prolactin drives cortical neuron maturation and dendritic development during murine embryonic stem cell differentiation - Martinez-Alarcon, Omar; Colin-Lagos, Daniela; Ramirez-Meza, Ximena; Castilla, Alejandra; Hernandez-Montes, Georgina; Flores-Garza, Eliezer; Lopez-Saavedra, Alejandro; Avila-Gonzalez, Daniela; Martinez-Juarez, Alejandro; Molina-Hernández, Anayansi; Diaz-Martinez, Nestor Emmanuel; Portillo, Wendy; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionProlactin (PRL) is a pleiotropic hormone implicated in various physiological processes; however, its contribution to neurodevelopment, particularly early corticogenesis, remains insufficiently characterized. In this study, we investigate PRL’s regulatory influence on the initial stages of cortical development, with an emphasis on its effects on neuronal and astrocytic differentiation.MethodsWe employed a standardized in vitro differentiation protocol to generate cortical neurons from mouse embryonic stem cells (mESCs). Prolactin receptor (PRLr) expression was evaluated in pluripotent stem cells, neural stem cells (NSCs), immature neurons, and mature neurons using both PCR and immunofluorescence. These analyses revealed dynamic changes in PRLr expression throughout the differentiation process. Additionally, cells were treated with varying concentrations of PRL during early and late differentiation phases, enabling assessment of its impact on neuronal phenotypic distribution and morphological complexity.ResultsEarly PRL administration significantly enhanced the population of β-tubulin III + immature neurons, promoting neuronal survival without altering NSC proliferation. Furthermore, PRL treatment increased the abundance of Tbr1 + and NeuN + neurons, augmented dendritic complexity, and accelerated neuronal maturation. In contrast, PRL exposure at later stages of neural differentiation did not yield comparable effects. Notably, PRL delayed the maturation of protoplasmic astrocytes, although the total astrocyte population was not affected.DiscussionThese findings highlight PRL’s pivotal role as a regulator of early corticogenesis by modulating neuronal survival, dendritic development, and astrocyte maturation. PRL thus emerges as a potential key factor in neurodevelopment, underscoring its importance in the hormonal regulation of neural differentiation and maturation. These insights may have broader implications for understanding the molecular and cellular mechanisms underlying normal and pathological neurodevelopment.